Penatalaksanaan Holistik Wanita Usia 26 Tahun Dengan Kekurangan Energi Kronis Melalui Pendekatan Dokter Keluarga di Wilayah Puskesmas Rajabasa Indah - Alia, Ega Chessa; Nyimas, Naflah Nadila; Saftarina, Fitria; Aprianna, Belinda (Medula, 2024)
Malnutrition in Pregnancy (ICD 10-O25) is a malnutrition problem cause by the lack of food or nourishment intake in a long period of time, up to years. One of the potential problem in long term macro malnutrition, specifically in pregnant women with ICD 10-O25 is give birth to Low Weight Baby (LWB), anemia and decreased immunity. In Indonesia, there are 17.3% pregnant women with ICD 10-O25. Lampung in particular, there are 13.6% pregnant women with ICD 10-O25. Therefor, it is crucial to comprehensively manage nutrition status, especially in pregnant women. Identify internal and external risk factors and clinical problems present in the patient. Apply a holistic and comprehensive family doctor approach according to the problems found in the patient and carry out medicine-based management. This study is descriptive study about case report. The primary data obtained through anamnesis, physical examination and a visit to the home. Secondary data were obtained from medical records of patients. The patient is a pregnant women with ICD 10-O25. The internal risk factor aspect in the patient is the patient's unhealthy eating and drinking patterns. Aspects of the patient's external factors due to lack of support and information from the family and the environment. Patients are given information about CED and healthy eating patterns. In addition, patients are assisted in applying their knowledge. The diagnosis enforcement and management with this patient has been done with family medical approach, several theories and latest researches. After intervention to the patient, the patient has better understanding and attempted to apply the knowledge. Furthermore, the patient’s Mid Upper Arm Circumference (MUAC) has been increased in the last evaluation visit.